When more isn’t better: Sperm competition decreases fertilization success and motile sperm in two sea urchin species - Kumpitsch, Luisa; Beckmann, Lara Maleen; Leder, Erica H.; Paredes, Estefanía; Langer, Lucas; Lifjeld, Jan Terje; N. Havenhand, Jonathan; González Fernández, Jose (University of Gothenburg, 2025)
Abstract of the paper "When more isn’t better: Sperm competition decreases fertilization success and motile sperm in two sea urchin species":

Fertilization is a fundamental process where sperm-egg fusion is essential to maintain life of most metazoans. In species with external fertilization - the ancestral mode of reproduction - sperm must locate eggs in the open water, often under conditions of intense sperm competition. This form of sexual selection has been extensively studied in internal fertilizers, where complete fertilization is common. However, our understanding of sperm competition in external fertilizers remains limited. To investigate how sperm competition affects fertilization success in external fertilizers, we conducted controlled experiments on two sea urchin species: Dendraster excentricus and Paracentrotus lividus. Eggs from a single female were exposed either to sperm from individual males (non-competitive treatment) or to a pooled sample from three males (sperm competition treatment). We measured fertilization success as the proportion of eggs fertilized after two hours and assessed sperm motility using two parameters: the percentage of motile sperm and curvilinear velocity (VCL). Our results show that sperm competition can reduce both fertilization success and the percentage of motile sperm compared to the non-competitive treatment. Additionally, variation in fertilization success among males within the same experiment suggests the presence of gamete compatibility effects. We suggest that chemical interactions via seminal fluid from competitors, or via competitive blocking of the sperm-binding site by incompatible sperm, may cause reduced motility and fertilization under sperm competition. These findings underscore the importance of understanding the complex mechanisms of fertilization, particularly in taxa that reproduce externally. Further research is needed to explore how sperm competition and gamete interactions shape reproductive success in the marine environment.

Description of files:

fertility_data_cleaned.csv: data on Dendraster excentricus fertilization success means for non-competitive- and sperm competition treatment; used for linear mixed-effects models and basic statistics

fertility_data_cleaned.xlsx : see above

Fertility_FHL_means.csv: used for plotting and calculate basic statistics

Fertility_FHL_means.xlsx : see above

fertility_vigo_cleaned.csv: data on Paracentrotus lividus fertilization success means for non-competitive- and sperm competition treatment; used for linear mixed-effects models and basic statistics , and to filter for 1500 and 7500 sperm/µl which was used for further analysis

fertility_vigo_cleaned.xlsx: see above

Fertility_Vigo_means.csv: calculate statistics

Fertility_Vigo_means.xlsx: see above

FHL_FandF2.txt: look at differences between post 2h- and 24h fertilization success in D. excentricus

motility_data_cleaned.csv : perm motility data on D. excentricus, used for linear-mixed effects models and basic statistics

motility_data_cleaned.xlsx: see above

Motility_Fertility_FHL_Means.csv: motility and fertilization data on D. excentricus, used to check if motility parameters affected fertilization success

Motility_Fertility_FHL_Means.xlsx: see above

Motility_Fertility_Vigo_Means.xlsx: : motility and fertilization data on P. lividus, used to check if motility parameters affected fertilization success

Motility_Fertility_Vigo_Means.csv: see above

Motility_Urchins.csv: used for plotting motility data in both sea urchin species

motility_vigo_cleaned.csv: sperm motility data on P. lividus

Size_Correlation_F.csv: test sizes and fertlilization success of both sea urchin species, to check if test size affects fertilzation success

Size_Correlation_M.csv: test sizes and fertlilization success of both sea urchin species, to check if test size affects sperm motility

Size_Correlation_M.xlsx: see above
Keywords: Evolutionary biology not elsewhere classified; Medical and Health Sciences; Medicin och hälsovetenskap; Evolutionary Biology; Evolutionsbiologi